2013
DOI: 10.1080/00207543.2013.852266
|View full text |Cite
|
Sign up to set email alerts
|

A forecast-driven tactical planning model for a serial manufacturing system

Abstract: Our work is motivated by real-world planning challenges faced by a manufacturer of industrial products. We study a multi-product serial-flow production line that operates in a low-volume, long lead-time environment. The objective is to minimize variable operating costs, in the face of forecast uncertainty, raw material arrival uncertainty and in-process failure. We develop a dynamic-programming-based tactical model to capture these key uncertainties and trade-offs, and to determine the minimum-cost operating t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 25 publications
0
5
0
1
Order By: Relevance
“…It was demonstrated that the accuracy of inventory prediction systems can be enhanced using the time series analysis of each component's demand [37]. A statistical multi-period prediction system was proposed by [38] to consider demand uncertainty and satisfy demand with minimal operating costs, which is achieved by incorporating a dynamic programming model for the optimal inventory policy determination. Gumus et al [39] employed a neurofuzzy system to predict demand and lead time to deploy the inventory efficiently.…”
Section: B Big Data Analytics In Inventory Managementmentioning
confidence: 99%
“…It was demonstrated that the accuracy of inventory prediction systems can be enhanced using the time series analysis of each component's demand [37]. A statistical multi-period prediction system was proposed by [38] to consider demand uncertainty and satisfy demand with minimal operating costs, which is achieved by incorporating a dynamic programming model for the optimal inventory policy determination. Gumus et al [39] employed a neurofuzzy system to predict demand and lead time to deploy the inventory efficiently.…”
Section: B Big Data Analytics In Inventory Managementmentioning
confidence: 99%
“…The author develops an approximate procedure to determine the release dates of all the components. Another stream of research views the planned leadtimes as a tactical decision to capture the trade-off between resource requirements and Work in Process in the light of demand uncertainty (Chhaochhria and Graves 2013;Teo et al 2011Teo et al , 2012.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Computer simulations allow us to test various types of production quickly. Computer simulation makes it possible to check many consequences of changes in production, processes and selects the most efficient way to streamline logistics in the near future [11]. Simulation can be used both before calculating the design of the production system and in order to optimize the production system and in the design of production processes, respectively.…”
Section: Introductionmentioning
confidence: 99%